Evaluation of nonlinear behavior and resisting capacity of reinforced concrete columns subjected to blast loads. (November 2018) - Park, Gang-Kyu; Kwak, Hyo-Gyoung; Filippou, Filip C.
Abstract: A numerical method to estimate the dynamic response of reinforced concrete (RC) columns subjected to axial and blast loads is introduced in this paper. Upon adopting Timoshenko's beam theory, both the flexural and direct shear behaviors are incorporated into the numerical formulation. The moment-curvature relationship of a reinforced concrete (RC) section is based on the construction of the bending stiffness and, in advance, a dynamic increase factor (DIF), usually defined in the stress-strain relations of concrete and steel, is newly designed to be defined in the moment-curvature relation. In addition to the description of the dynamic characteristics in the RC section, additional modification of the moment-curvature relation is also performed to exactly simulate the large plastic deformation concentrated at the mid-span or beam-column joint due to the bond-slip or anchorage slip after yielding of the main reinforcement. Finally, the validity of the proposed method is verified by comparing the analytical results with the experimental data, and then the pressure-impulse (P–I) diagrams are constructed and compared to review the change in the resisting capacity of a RC column according to the variation of the axial force and slenderness ratio. Highlights: A numerical model incorporating the flexural behavior and the direct shear behavior is proposed. A dynamic increase factor (DIF) for the moment-curvature relationship is newly designed. The verification of the numerical model is performed through comparison with experimental data. A parametric study of RC column is performed to review the influence of the parameters.